The reliability of SketchAndCalcTM Area Calculator software in evaluating the obturated surface area of mandibular premolars and molars - Mustaffa, Musliana; Mat Yasin, Nur Madihah; Imam Sopingi, Shuhadatul Hasanah; Mohd Ibrahim, Mohamad Shafiq (IIUM Press, 2023)
INTRODUCTION: The measurement consistency of an assessment tool in biomedical research is important for validation of data. This study aims to determine the reliability of SketchAndCalcTM Area Calculator software in evaluating the obturated surface area of single rooted mandibular premolars and mandibular first molars between two examiners and to compare with the previous studies. MATERIALS AND METHODS: 30 scanning electron microscopy (SEM) images of extracted single rooted mandibular premolars and 30 SEM images of mandibular first molars were obtained from the previous studies. The extracted teeth were previously obturated with GuttaFlow Bioseal. Calibration between two examiners was done prior to start of the study. SketchAndCalcTM Area Calculator software was used to evaluate the volumetric percentage of obturated surface area. Inter- examiner reliability was determined between two examiners and compared to the previous studies using Intraclass Correlation Coefficient (ICC) with the following categories; ICC<0.50: poor reliability, ICC 0.50-0.75: moderate reliability, ICC 0.75-0.90: good reliability, ICC>0.9: excellent reliability. The data was analysed with SPSS version 25.0. RESULTS: The ICC values between two examiners were 0.979 in mandibular premolars and 0.918 in mandibular molars. Meanwhile, the ICC values between two examiners and to the previous studies were 0.844 in mandibular premolars and 0.962 in mandibular molars. CONCLUSIONS: Excellent inter-examiner reliability was observed in premolars and molars, however when compared to the previous studies, good and excellent inter- examiner reliability were observed in premolars and molars respectively.